Multifunctional ethyl cellulose composite material and preparation method thereof
By combining ethyl cellulose with glycerol and new composite nanotitanium dioxide, a multifunctional ethyl cellulose composite material was prepared, which solved the shortcomings of existing materials in terms of mechanical properties, ductility, hydrophobicity, ultraviolet barrier, antibacterial and ammonia-sensitive discoloration, and achieved the versatility and wide application of the materials.
Patent Information
- Application Number
- CN202411956712.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2025-03-28
AI Technical Summary
The existing ethyl cellulose materials have shortcomings in mechanical properties, ductility, hydrophobicity, ultraviolet barrier, antibacterial and ammonia-sensitive discoloration, which limits their application in food packaging, smart materials and other fields.
A multifunctional ethyl cellulose composite material was prepared by combining ethyl cellulose with glycerol and novel composite nanotitanium dioxide. The method of preparing the composite material includes blending nanotitanium dioxide with ferrous sulfate heptahydrate and syringeic acid, followed by mixing with ethyl cellulose and glycerol to form a uniform film forming liquid, and drying to obtain the final composite material.
This multifunctional ethyl cellulose composite material exhibits excellent mechanical strength, ductility, hydrophobicity, ultraviolet barrier, antibacterial and ammonia-sensitive discoloration properties, and is suitable for food packaging, smart materials, antibacterial materials and other fields. Its preparation process is simple, environmentally friendly, low-cost, and is suitable for large-scale production.
Smart Images

Figure CN119708647A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a multifunctional ethyl cellulose composite material and a preparation method thereof. Background Art
[0002] Ethyl cellulose is a typical natural polysaccharide derivative obtained by etherification of cellulose. It has a wide range of sources, is renewable, has excellent film-forming properties, light transmittance and biodegradability, and is one of the most promising natural biodegradable materials. Ethyl cellulose is stable when exposed to light, heat, oxygen, water or chemicals, and is widely used in the fields of films, thickeners and adhesives in the food, pharmaceutical and papermaking industries. In addition, ethyl cellulose molecules contain many oxygen-containing groups, which makes this compound have good hydrophilicity. However, good hydrophilicity makes ethyl cellulose-based materials easily infiltrated by solutions such as water, which makes their own structure and properties easily destroyed, limiting their scope of application. In addition, the mechanical properties of ethyl cellulose materials are poor, and they will be brittle and easy to break. In addition, they are lacking in functions such as UV blocking, antibacterial, and ammonia-sensitive color change, which limits their application in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety, etc. At present, most of the research focuses on improving the thermal properties, mechanical properties and water resistance of ethyl cellulose composites, but few studies report how to simultaneously improve the mechanical strength, ductility, hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change properties and functions of ethyl cellulose. Therefore, how to simultaneously improve the mechanical strength, ductility, hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change properties and functions of ethyl cellulose so that it can be used in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields is a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a multifunctional ethyl cellulose composite material and a preparation method thereof. The multifunctional ethyl cellulose composite material has excellent mechanical strength, ductility, hydrophobicity, ultraviolet blocking, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, suitable for scaled-up production, and is suitable for food packaging, smart materials, antibacterial materials, ultraviolet protection, ammonia detection, environmental monitoring and safety and other fields.
[0004] Technical solution of the present invention:
[0005] A multifunctional ethyl cellulose composite material, characterized in that it is composed of the following components in parts by weight: 100 parts of ethyl cellulose, 10 parts of a plasticizer, and 2-8 parts of a novel composite nano titanium dioxide;
[0006] The plasticizer is glycerol;
[0007] The preparation method of the novel composite nano titanium dioxide comprises the following steps:
[0008] (1) Disperse 30 parts of nano-titanium dioxide in 2000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform titanium dioxide dispersion for later use;
[0009] (2) Take 44.48 parts of ferrous sulfate heptahydrate, add it to the titanium dioxide dispersion obtained in step (1), and stir at room temperature for 60 minutes to obtain a uniform mixed solution for later use;
[0010] (3) Take 15.85 parts of syringic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform syringic acid solution for later use;
[0011] (4) Add the syringic acid solution obtained in step (3) to the mixed solution obtained in step (2), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain a novel composite nano-titanium dioxide.
[0012] The present invention also provides a method for preparing the multifunctional ethyl cellulose composite material, which is characterized by comprising the following steps:
[0013] (1) Add 100 parts of ethyl cellulose and 10 parts of plasticizer to 1500 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;
[0014] (2) Dispersing 2-8 parts of the novel composite nano-titanium dioxide in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0015] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 20 min to obtain a uniform film-forming solution for later use;
[0016] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 50° C. for 24 h to obtain a multifunctional ethyl cellulose composite material.
[0017] The application of the multifunctional ethyl cellulose composite material is characterized in that it is used in the fields of food packaging, smart materials, antibacterial materials, ultraviolet protection, ammonia detection, environmental monitoring and safety, etc.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The multifunctional ethyl cellulose composite material prepared by the present invention has excellent mechanical strength, ductility, hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the novel composite nano titanium dioxide involved in the present invention;
[0021] Figure 2 These are actual photos of the ethyl cellulose prepared in Comparative Example 1 and the multifunctional ethyl cellulose composite material samples prepared in Example. DETAILED DESCRIPTION
[0022] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above content of the present invention. The parts of the raw materials are all parts by weight unless otherwise specified.
[0023] In the following specific embodiments and comparative example formulas and preparation methods, the ethyl cellulose used is a product provided by McLean Biochemical Technology Co., Ltd. (CAS No.: 9004-57-3); the nano titanium dioxide used is a product provided by Roan Reagent Co., Ltd. (its specifications: Jinhong hydrophilic high-purity reagent, purity of 99.8%, particle size of 40nm); the syringic acid used is an analytically pure reagent provided by Shanghai Yien Chemical Technology Co., Ltd.; ferrous sulfate heptahydrate and glycerol are analytically pure reagents provided by Xilong Scientific Co., Ltd.
[0024] In the following specific embodiments and comparative examples, the preparation method of the novel composite nano titanium dioxide comprises the following steps:
[0025] (1) Disperse 30 parts of nano-titanium dioxide in 2000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform titanium dioxide dispersion for later use;
[0026] (2) Take 44.48 parts of ferrous sulfate heptahydrate, add it to the titanium dioxide dispersion obtained in step (1), and stir at room temperature for 60 minutes to obtain a uniform mixed solution for later use;
[0027] (3) Take 15.85 parts of syringic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform syringic acid solution for later use;
[0028] (4) Add the syringic acid solution obtained in step (3) to the mixed solution obtained in step (2), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain a novel composite nano-titanium dioxide.
[0029] Example 1
[0030] A multifunctional ethyl cellulose composite material is characterized by being composed of the following components in parts by weight: 100 parts of ethyl cellulose, 10 parts of glycerol, and 2 parts of new composite nano titanium dioxide.
[0031] The preparation method comprises the following steps:
[0032] (1) Add 100 parts of ethyl cellulose and 10 parts of glycerol to 1500 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;
[0033] (2) Dispersing 2 parts of the novel composite nano-titanium dioxide in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0034] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 20 min to obtain a uniform film-forming solution for later use;
[0035] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 50° C. for 24 h to obtain a multifunctional ethyl cellulose composite material.
[0036] Example 2
[0037] A multifunctional ethyl cellulose composite material is characterized by being composed of the following components in parts by weight: 100 parts of ethyl cellulose, 10 parts of glycerol, and 5 parts of new composite nano titanium dioxide.
[0038] The preparation method comprises the following steps:
[0039] (1) Add 100 parts of ethyl cellulose and 10 parts of glycerol to 1500 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;
[0040] (2) Dispersing 5 parts of the novel composite nano-titanium dioxide in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0041] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 20 min to obtain a uniform film-forming solution for later use;
[0042] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 50° C. for 24 h to obtain a multifunctional ethyl cellulose composite material.
[0043] Example 3
[0044] A multifunctional ethyl cellulose composite material is characterized by being composed of the following components in parts by weight: 100 parts of ethyl cellulose, 10 parts of glycerol, and 8 parts of new composite nano titanium dioxide.
[0045] The preparation method comprises the following steps:
[0046] (1) Add 100 parts of ethyl cellulose and 10 parts of glycerol to 1500 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;
[0047] (2) Dispersing 8 parts of the novel composite nano-titanium dioxide in 500 parts of ethanol to obtain a uniform dispersion for later use;
[0048] (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 20 min to obtain a uniform film-forming solution for later use;
[0049] (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 50° C. for 24 h to obtain a multifunctional ethyl cellulose composite material.
[0050] Comparative Example
[0051] As a comparison standard of the above embodiments, the present invention provides an ethyl cellulose material prepared without the novel composite nano titanium dioxide, comprising the following steps:
[0052] (1) Add 100 parts of ethyl cellulose and 10 parts of glycerol to 1500 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside;
[0053] (2) Add 500 parts of ethanol to the blended solution obtained in step (1), and stir at room temperature for 20 min to obtain a uniform film-forming solution for later use;
[0054] (3) The film-forming solution obtained in step (2) is poured into a flat-bottomed dish and dried in an oven at 50° C. for 24 h to obtain ethyl cellulose material.
[0055] Structure and performance test:
[0056] The ethyl cellulose material prepared in the above comparative example and the multifunctional ethyl cellulose composite material prepared in the embodiment were subjected to performance tests, wherein the UV-visible properties were tested by UV-visible spectrometer, and the average UV transmittance was calculated with reference to GB / T18830-2009; hydrophobicity characterization: the water contact angle of the sample material was measured by a static contact angle tester; the tensile properties were tested by an electronic tensile testing machine (LDW-2G); the antibacterial property of the material was tested in accordance with QBT2591 2003; the ammonia response test method was as follows: the sample material was exposed to an ammonia environment for 10 minutes, the color change of the sample material was observed and recorded, and the color difference value ∆E of the sample material before and after the ammonia response was calculated (Note: ∆E >3 indicates an obvious color change visible to the human eye).
[0057] The above performance test data is shown in Table 1.
[0058] Table 1 Sample performance test data
[0059]
[0060] The results of the ammonia response test experiment show that the ethyl cellulose material prepared in the comparative example is colorless and transparent. After being exposed to an ammonia environment for 10 minutes, its color does not change, and it still exhibits colorless and transparent optical properties, and its ∆E value is 2.41 (that is, the color difference is negligible and cannot be distinguished by the human eye). The multifunctional ethyl cellulose composite material prepared in Example 3 is yellow. After being exposed to an ammonia environment for 10 minutes, its color changes significantly (from yellow to brown), and its ∆E value is as high as 24.49 (Note: ∆E >3 indicates a significant color change visible to the human eye).
[0061] The results of the antibacterial test experiments show that the ethyl cellulose material prepared in the comparative example does not show obvious antibacterial activity against Escherichia coli and Staphylococcus aureus, while the multifunctional ethyl cellulose composite material prepared in Example 3 has an inhibition rate of more than 99% against Escherichia coli and Staphylococcus aureus, that is, the multifunctional ethyl cellulose composite material prepared in the example has excellent antibacterial activity.
[0062] In summary, it can be seen from the sample performance test data (see Table 1) that the multifunctional ethyl cellulose composite material prepared by the present invention has excellent mechanical strength, tensile elongation at break (i.e., ductility), hydrophobicity, UV blocking, antibacterial and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety and other fields.
[0063] The content of the present invention is not limited to the embodiments listed, and any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the description of the present invention are covered by the claims of the present invention.
Claims
1. A multifunctional ethyl cellulose composite material, characterized in that: The invention is composed of the following components in parts by weight: 100 parts of ethyl cellulose, 10 parts of plasticizer, and 2-8 parts of novel composite nano titanium dioxide; The plasticizer is glycerol; The preparation method of the novel composite nano titanium dioxide comprises the following steps: (1) Disperse 30 parts of nano-titanium dioxide in 2000 parts of deionized water, stir at room temperature for 10 minutes to obtain a uniform titanium dioxide dispersion for later use; (2) Take 44.48 parts of ferrous sulfate heptahydrate, add it to the titanium dioxide dispersion obtained in step (1), and stir at room temperature for 60 minutes to obtain a uniform mixed solution for later use; (3) Take 15.85 parts of syringic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform syringic acid solution for later use; (4) Add the syringic acid solution obtained in step (3) to the mixed solution obtained in step (2), stir and react at room temperature for 20 min, then centrifuge, wash and dry in sequence to obtain a novel composite nano-titanium dioxide.
2. The method for preparing a multifunctional ethyl cellulose composite material according to claim 1, characterized in that The steps include: (1) Add 100 parts of ethyl cellulose and 10 parts of plasticizer to 1500 parts of ethanol, stir at 50°C for 20 min to obtain a uniform blend solution, cool to room temperature and set aside; (2) Dispersing 2-8 parts of the novel composite nano-titanium dioxide in 500 parts of ethanol to obtain a uniform dispersion for later use; (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at room temperature for 20 min to obtain a uniform film-forming solution for later use; (4) The film-forming solution obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 50° C. for 24 h to obtain a multifunctional ethyl cellulose composite material.
3. The use of a multifunctional ethyl cellulose composite material according to claim 1, characterized in that: Used in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety fields.